ТАБИИЙ ГАЗНИ АДСОРБЦИЯ УСУЛИДА ҚУРИТИШ ТЕХНОЛОГИК СХЕМАСИНИ ИШЛАБ ЧИҚИШ - Махмудов, М.Ж.; Неъматов, Ҳ.И. (SCIENCE and SOCIETY, 2022)
In this article, a technological scheme for drying natural gas has been developed, according to this technological scheme, if the process of drying natural gas is carried out in one adsorber, then the regeneration process using hot gas is carried out in the other, and in the drying process using unheated gas is carried out by creating a cycle using a compressor.